The relationship among safety leadership, risk perception, safety culture, and safety performance: Military volunteer soldiers as a case study - Wei, Siao-Yun; Kuo, Yen-Ku (Frontiers in Psychology, 2023)
Safety is fundamental to any organization; if not based on safety, organizational decision-making and management would be meaningless. For a country, soldiers are responsible for national security; they serve as a barrier that defends a country against external invasive forces, thus assuming great missions and responsibilities on their shoulders. To ensure soldiers fulfill their duties of protecting the country and the people, they should gain clear risk perception, which should be instilled into them during their daily combat readiness training. Only when their performances meet safety criteria can they become a strong fighting force. This study recruited military volunteer soldiers as its research participants and employed convenience sampling to distribute questionnaires. In total, this research collected 725 valid copies, of which the data were used to explore the relationship among safety leadership, risk perception, safety culture and safety performance. To achieve this goal, this study proposed some research hypotheses based on literature review. The hypotheses were all verified via latent variable modeling and multiple hierarchical regression analysis after the reliability and validity of each construct had been tested via confirmatory factor analysis. The research results showed that the more deeply military volunteer soldiers sense safety leadership, the clearer their risk perception will be and the more helpful it would be in achieving safety performance. It is worth mentioning that risk perception can serve as a mediator while safety culture can mediate the relationship between safety leadership and safety performance. Lastly, the research proposes suggestions in the section of conclusions, which provides reference to the combat readiness training and daily tasks of soldiers.